(8-6i)-4=x-(1+yi)

Simple and best practice solution for (8-6i)-4=x-(1+yi) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (8-6i)-4=x-(1+yi) equation:


Simplifying
(8 + -6i) + -4 = x + -1(1 + yi)

Remove parenthesis around (8 + -6i)
8 + -6i + -4 = x + -1(1 + yi)

Reorder the terms:
8 + -4 + -6i = x + -1(1 + yi)

Combine like terms: 8 + -4 = 4
4 + -6i = x + -1(1 + yi)
4 + -6i = x + (1 * -1 + iy * -1)
4 + -6i = x + (-1 + -1iy)

Reorder the terms:
4 + -6i = -1 + -1iy + x

Solving
4 + -6i = -1 + -1iy + x

Solving for variable 'i'.

Move all terms containing i to the left, all other terms to the right.

Add 'iy' to each side of the equation.
4 + -6i + iy = -1 + -1iy + iy + x

Combine like terms: -1iy + iy = 0
4 + -6i + iy = -1 + 0 + x
4 + -6i + iy = -1 + x

Add '-4' to each side of the equation.
4 + -6i + -4 + iy = -1 + -4 + x

Reorder the terms:
4 + -4 + -6i + iy = -1 + -4 + x

Combine like terms: 4 + -4 = 0
0 + -6i + iy = -1 + -4 + x
-6i + iy = -1 + -4 + x

Combine like terms: -1 + -4 = -5
-6i + iy = -5 + x

Reorder the terms:
5 + -6i + iy + -1x = -5 + x + 5 + -1x

Reorder the terms:
5 + -6i + iy + -1x = -5 + 5 + x + -1x

Combine like terms: -5 + 5 = 0
5 + -6i + iy + -1x = 0 + x + -1x
5 + -6i + iy + -1x = x + -1x

Combine like terms: x + -1x = 0
5 + -6i + iy + -1x = 0

The solution to this equation could not be determined.

See similar equations:

| -3(2p+14)-28=2(p+15)+12 | | 6x-3=4(x+22) | | -11+4n=5-(11+17) | | (x^3-x^2-2)=0 | | .7(-3X-2)=3.5+1 | | -11+4n=5-(11+12) | | 6x+-10=110 | | 5x(x^3-x^2-2)=0 | | 20+2.50(19)=x | | 20+2.50(20)=x | | 20+2.50(18)=x | | 20+30+p=180 | | -9.1=k-6.3 | | 20+2.50(17)=x | | 3.2+d=5 | | 5x^2+41x-54=0 | | 20+2.50(16)=x | | 7(n-7)(8n-7)=0 | | 2x-2(x+1)=3 | | 60+19x+5.75x=159 | | -30=j-10+11j | | 3y-6=-2y-6 | | 180-(19x+4)=y | | (4x+3)(3x^2+3x+1)= | | 3m-4=6m | | 1d/2d-3/4=3d/5D | | R=s-5 | | 20+2.50(15)=x | | 10=.25(b-12) | | 12(2x+3)-3(i+7x)=0 | | -3m+5(1+m)=6+2m | | 12t^2-7t+1=0 |

Equations solver categories